Phenotypic and oncological insights in ANNA1 autoimmunity: Age stratification and biomarker analysis - Naveen Kumar Paramasivan; Majed Masoud; Carley Karsten; Anza Zahid; Haidara Kherbek; Anastasia Zekeridou; Sri Raghav Sista; Surendra Dasari; Andrew M. Knight; Georgios Mangioris; John R. Mills; Andrew McKeon; et al. (Annals of Clinical and Translational Neurology)
Abstract Objective To describe the phenotypes, oncological associations, biomarker profiles, and outcomes across different age groups in patients with ANNA1 (anti‐Hu) autoimmunity. Methods A retrospective review of patients with ANNA1‐IgG in serum/CSF between January 1, 2001, and December 31,2019 was performed. Patients were classified into three groups based on the age of symptom onset. Phage immunoprecipitation sequencing (PhIP‐Seq) and neurofilament light chain (NfL) measurements were done in patient sera/CSF with archived samples. Results Of 122 patients, 81 (66%), 20 (16%), and 21 (17%) patients belonged to older adults, young adults, and pediatric groups, respectively. Lung cancer and neuromuscular presentations were more common in older adults (p < 0.001), while limbic encephalitis and neuroblastoma were more common in pediatric patients (p < 0.005). Most young adults (75%) did not have cancer identified. Proportions of patients with a favorable response to immunotherapy were 20%, 30%, and 52% among older adults, young adults, and pediatric groups, respectively. PhIP‐Seq demonstrated significant enrichment for ELAVL4 peptides especially for amino acids 240–289, in the majority of samples evaluated (36/67, 54%). ZIC and SOX2 peptides were significantly enriched in those with central nervous system presentations. Serum NfL levels were elevated in patients with cancer and those with poor long‐term outcomes. Interpretation Young adults with ANNA1 autoimmunity phenotypically resembled older adults but rarely had an underlying cancer. Pediatric patients frequently presented with limbic encephalitis and neuroblastoma and often responded favorably to immunotherapy. Distinct antigenic signatures may underlie differences in clinical presentations. Serum NfL levels may be a biomarker of poor long‐term outcomes in ANNA1 autoimmunity.